2020
DOI: 10.1111/jsr.13201
|View full text |Cite
|
Sign up to set email alerts
|

Maternal perceptions of sleep problems among children and mothers during the coronavirus disease 2019 (COVID‐19) pandemic in Israel

Abstract: Despite the marked impact of the coronavirus disease 2019 (COVID‐19) pandemic on the life of families and its possible negative implications for sleep, little is known about how sleep among parents and children has been impacted by this current crisis. In the present study, we addressed, for the first time, possible consequences of the COVID‐19 crisis and home confinement on maternal anxiety, maternal insomnia, and maternal reports of sleep problems among children aged 6–72 months in Israel ( N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
93
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(110 citation statements)
references
References 21 publications
8
93
0
3
Order By: Relevance
“…Liu et al[ 5 ] described an increase in total sleep duration also in preschoolers. However, data on sleep duration in preschoolers are inconsistent across studies because an Israelian research on infants and children aged 6-72 months reported variable changes in sleep duration, either increase, or decrease or no changes[ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al[ 5 ] described an increase in total sleep duration also in preschoolers. However, data on sleep duration in preschoolers are inconsistent across studies because an Israelian research on infants and children aged 6-72 months reported variable changes in sleep duration, either increase, or decrease or no changes[ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results can be interpreted in line with the idea that in mothers, emotional weaknesses, such as depressive symptoms and stress, are often associated with sleep difficulties in children ( Stoléru et al., 1997 ). It is also possible that mothers with poor emotional regulation tend to identify their children as more problematic and symptomatic ( Zreik et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, literature suggests that children are more likely to experience emotional or behavioral difficulties if at least one parent works on irregular schedules both in ordinary and in pandemic scenarios ( Manzo & Minello, 2020 ; Rönkä et al., 2017 ). Also, the exposure of children to maternal psychological difficulties may lead to negative outcomes such as internalizing or externalizing symptoms, delays in development goals, and sleep problems ( Zreik et al., 2020 ). This pattern may be more relevant for school-age children.…”
Section: Introductionmentioning
confidence: 99%
“…Further research is also needed to examine stressors and specific resilience pathways for families who may be at increased risk for mental health impacts through COVID-19, including families of children with special needs (Asbury et al, 2020) or with health problems (Fontanesi et al, 2020;Yuan et al, 2020), low-income families, and families where a parent is an essential worker (Coyne et al, 2020). In addition, COVID-19 presents a number of hardships that were not able to be measured within the current survey (e.g., sleep difficulties; Zreik et al, 2020) and should be explored in future research.…”
Section: Discussionmentioning
confidence: 99%